Post-Modernism, Deconstruction of Christian Religious Education, and Cultural Projection in Central Kalimantan - Alfonso Munte (STABN RADEN WIJAYA WONOGIRI, 2024)
The purpose of this research is to examine cultural participation in Central Kalimantan in the context of Christian education, whether as a curriculum, subject, or livelihood of Christian learning, in the midst of the postmodern wave. The aim is to explore postmodernist ideas in Christian education that are non-totalitarian, acknowledge the non-homogeneity of truth, and allow for diversity and freedom of thought. This research method prioritizes postmodernist thinking and culture in Christian religious education through a literature study. Secondary sources are taken from journal references (Scopus and Sinta) and several dissertations related to Christian education. The main sources for analysis are books by Karl Henri Nouwen, Franz-Magnis Suseno, Polanyi, and Jean-François Lyotard. The language used is clear, objective, and value-neutral, with a formal register and precise word choice. The logical structure ensures a clear and concise flow of information with causal connections between statements. The text is free from grammatical errors, spelling mistakes, and punctuation errors. The text adheres to conventional structure and formatting features, with consistent citation and footnote style. No changes in content have been made. The results indicate that postmodernism, which rejects grand narratives and totalitarianism, as well as the omission of imperialism in Christian education, plays a role in the form of a living culture in Central Kalimantan. This culture emphasizes the balance of life, respect for creation, and the ritualistic and spiritual sacredness of religion, which are reflected in education, including Christian education